The Shadows of Society: Class and Conflict in the Plays of John Osborne - Khudhair Sabr, Dr. Basim (Journal of Innovation in Education and Social Research, 2025)
This article hopes to loosen up the astounding depictions of class and battle in the plays of renowned producer, John Osborne, highlighting their ideas for understanding post-war English society. The fundamental objective is to examine the intricacies of how Osborne's plays address class capabilities and social tensions. A mixed procedure approach was taken on, consolidating scholarly assessment of Osborne's critical works, undeniable documentation from post-war Britain, and contemporary execution place studies. The plays were destitute down concerning account structure, character headway, and trade to find their portrayals of class and battle. The revelations uncover that Osborne's plays are significantly embedded in the socio-social types of their time, strikingly portraying the trepidation and disappointment of lower and common laborers. His characters habitually grapple with vibes of trap, discontent, and a yearning for transportability, highlighting the varieties and discontents of English society. These subjects resounded fundamentally with swarms, adding to the plays' questionable nature and accomplishment. Osborne's depiction of class isn't just a sensational saying; it is critical of the developments and challenges faced by post-war English society. The plays, in various ways, mirror the discontent of an overall population on the move, uncovering an understanding of the lived experiences of individuals who got inside out-of-date class structures. John Osborne's plays go about as serious areas of strength for a highlight to see and grasp the penchants of class battle and social changes in post-war Britain. Through his rough, unfiltered portrayal of characters and their fights, Osborne not only assesses the rigid class plans of his time but also exalts the voices and shadows of an overall population grappling with its own character.